La restauration du patrimoine et ses enjeux - Claudie Voisenat (In Situ)
This lecture was delivered at the opening of the 12th days of restoration-conservation (30 and 31 March 2023). It offers an analysis of the issues involved in restoration and the different manners of ‘living heritage’. If restoration is undoubtedly a central feature in the memory paradigm that is at the foundations of the relations our contemporary societies have with their heritage, its links with the question of the past and with memory is infinitely complex.